Tumbuh Tanpa Ayah: Studi Korelasi Ketidakhadiran Ayah dan Self-Esteem Dewasa Awal - Beti Malia Rahma Hidayati; Alfiyaturrohmah (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Indonesia ranks third globally in the prevalence of fatherlessness, a phenomenon that significantly impacts children's psychological development. This study aims to analyze the influence of father absence (fatherless) on self-esteem during emerging adulthood (ages 18–25). Using a quantitative approach with a simple linear regression design, the study involved 100 respondents in Telukjambe Timur, Karawang, selected through questionnaire distribution. Data were processed using IBM SPSS version 27 to test validity, reliability, and the significance of the relationship between variables. The results indicate that the majority of respondents experienced moderate (44%) to high (35%) levels of fatherlessness. Correspondingly, 29% of respondents exhibited low to very low levels of self-esteem. Regression analysis confirmed a significant influence between fatherlessness and self-esteem (p = 0.001; R = 0.224), demonstrating that higher levels of fatherlessness correlate with lower self-esteem. These findings underscore the critical importance of paternal involvement in child-rearing to strengthen self-esteem during the transition to adulthood and highlight the need for psychological support for individuals experiencing father absence.